Strategi Bertahan Hidup Tenaga Kerja Musiman Di PTPN VII Cinta Manis Kabupaten Ogan Ilir: Strategi Bertahan Hidup Tenaga Kerja Musiman Di PTPN VII Cinta Manis Kabupaten Ogan Ilir - Aprianti, Ririn (Pusat Kajian Demografi, Etnografi dan Transformasi Sosial, 2024)
This research aims to describe the survival strategy of seasonal workers in PTPN VII Cinta Manis Ogan Ilir Regency. This research uses two types of data, namely primary data and secondary data. The selection of informants uses snowball sampling method. The data analysis method used in this research is descriptive method through qualitative approach. The results showed that the socioeconomic conditions of seasonal workers are still fairly low, this can be seen based on the limitations of education, employment, income, residence, and also health services. Seasonal workers in PTPN VII Cinta Manis apply several strategies to survive, namely: 1) Tying the belt tighter, seasonal workers make savings on expenses by reducing the budget for food needs. 2) Alternative subsistence ethics, done by looking for side jobs and asking for help from family members to increase family income. 3) Social relations/social networks, which are applied by establishing relationships with stall owners when they need basic needs. In addition, they also ask for help from relatives and foremen when experiencing economic difficulties.